THE EFFECT OF MOUTH RINSES ON THE COLOR STABILITY OF SONICFILL AND A NANOHYBRID COMPOSITE - Tuğba Toz-Akalın; Gencay Genç; Yonca Korkmaz-Ceyhan; Funda Öztürk-Bozkurt (Istanbul University, 2016)
Purpose: The aim of this study was to evaluate the effects of 4 mouth rinses on the color stability of two different resin composites. Materials and Methods: A2 shade sonic-activated bulk fill material SonicFill (Kerr) and conventional nanohybrid composite Filtek Z550 (3M ESPE) were used. Forty disc-shaped specimens (10 mm x 2 mm) were fabricated for both composites and finished using 400-grit SiC paper and polished. After polishing and immersing in distilled water for 24h all specimens were subjected to color measurements. The baseline color values (L*, a*, b*) of each specimen were measured with a colorimeter. Following baseline measurement each composite group was divided into 5 groups: Oral-B Pro Expert Clinic Line Alcoholfree (Oral-B) group, Listerine Tooth Defense Rinse (Listerine) group, Pharmol Zn Mouth rinse (Çözümilaç) group, Nilera Mouth rinse (Nilera) group and Distilled water (control) group. The specimens were incubated in mouth rinses (20 ml) at 37°C for 12 hours and subjected to color measurement. Two-way ANO VA was used for statistical analysis (p<0.05). Results: SonicFill showed significantly higher discoloration when exposed to Oral-B Pro Expert Clinic Line Alcohol-free, Listerine Tooth Defense Rinse and Pharmol Zn Mouth rinse. The color differences of two resin composites were not statistically significant for distilled water and Nilera Mouth rinse. Conclusion: Within the limits of this study it can be concluded that the SonicFill showed higher discoloration than nanohybrid resin composite Filtek Z550.